2016
DOI: 10.3892/mmr.2016.5232
|View full text |Cite
|
Sign up to set email alerts
|

Embelin induces apoptosis of human gastric carcinoma through inhibition of p38 MAPK and NF-κB signaling pathways

Abstract: Embelin is a small-molecule inhibitor of X‑linked inhibitor of apoptosis protein (XIAP), and it induces apoptosis in tumor cells via the inhibition of XIAP. The aim of the present study was to investigate the anticancer effect of embelin on human gastric carcinoma cells and the mechanisms underlying this effect. Cell proliferation of SGC7901 human gastric carcinoma cells was measured using MTT assay, following treatment with embelin (5, 10 and 15 µM) on days 1, 3 and 5. Caspase‑3 and nuclear factor (NF)‑κB p65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…In addition, it alters musclespecific gene expression in HEK 293T cells [194]. Notably, embelin was not directly related to anti-cancer activity upon HAT inhibition yet, but it is associated with proapoptotic effects in prostate cancer cells (PC-3, DU145, LNCaP-LN3) mediated through modulation of Akt and β-catenin signaling and moreover induces apoptosis in human gastric carcinoma through alteration of p38 MAPK and NF-κB signaling pathways [195,196]. In addition, embelin inhibits cell proliferation, induces apoptosis, and alters expression of pivotal oncogenes in MCF-7 and MDA-MB-231 breast cancer cells [197].…”
Section: Embelin -Pcafmentioning
confidence: 99%
“…In addition, it alters musclespecific gene expression in HEK 293T cells [194]. Notably, embelin was not directly related to anti-cancer activity upon HAT inhibition yet, but it is associated with proapoptotic effects in prostate cancer cells (PC-3, DU145, LNCaP-LN3) mediated through modulation of Akt and β-catenin signaling and moreover induces apoptosis in human gastric carcinoma through alteration of p38 MAPK and NF-κB signaling pathways [195,196]. In addition, embelin inhibits cell proliferation, induces apoptosis, and alters expression of pivotal oncogenes in MCF-7 and MDA-MB-231 breast cancer cells [197].…”
Section: Embelin -Pcafmentioning
confidence: 99%
“…Its activation regulates a variety of cellular behaviors such as cell proliferation, differentiation, and apoptosis. The MAPK signaling pathway, including members p38 and ERK, plays a key role in the ability of bone marrow mesenchymal stem cells to differentiate into osteogenic cells (Jaiswal et al, 2000;Liu et al, 2009), and is related to cell self-renewal (Wang et al, 2016;Xu et al, 2016). Hypoxia can activate the p38/ MAPK and MAPK/ERK signaling pathways (Qiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study demonstrated that embelin suppressed p-p38 and NF-κB protein expression in AAA mice. Xu et al (14) suggested that embelin induces apoptosis through inhibition of p38 MAPK and NF-κB signaling pathways in human gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research revealed that embelin also has antioxidant, hepato-protective, antibacterial, anti-diabetic, and anti-inflammatory effects in other organs (12,13). Embelin additionally blocks the NF-ΚB signaling pathway that is the key protein associated with the ischemia-reperfusion injury-induced inflammatory response (14). The aim of the present study was to elucidate how embelin inhibits AAA and its underlying molecular mechanism.…”
Section: Introductionmentioning
confidence: 92%